Catalyst-free visible-light-initiated oxidative coupling of aryldiazo sulfones with thiols leading to unsymmetrical sulfoxides in air - Liu, Qishun; Wang, Leilei; Yue, Huilan; Li, Jiang-Sheng; Luo, Zidan; Wei, Wei (Green chemistry : an international journal and green chemistry resource : GC, 2019)
A facile and efficient visible-light-driven method has been developed to construct sulfoxides via oxidative coupling of aryldiazo sulfones with thiols using the O 2 in air as the oxidant. This reaction could be performed at room temperature under catalyst- and additive-free conditions. The present methodology offers a mild and environmentally benign approach to obtain a library of sulfoxides in good yields with favorable functional group tolerance. A facile visible-light-driven method has been developed to construct sulfoxides from aryldiazo sulfones and thiols in air under photocatalyst-free conditions.